2018
DOI: 10.1530/joe-18-0282
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone controls lipolysis by regulation of FSP27 expression

Abstract: Growth hormone (GH) has long been known to stimulate lipolysis and insulin resistance; however, the molecular mechanisms underlying these effects are unknown. In the present study, we demonstrate that GH acutely induces lipolysis in cultured adipocytes. This effect is secondary to the reduced expression of a negative regulator of lipolysis, Fat Specific Protein 27 (FSP27) at both the mRNA and protein level. These effects are mimicked in vivo as transgenic over-expression of GH leads to a reduction of FSP27 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 70 publications
4
23
0
Order By: Relevance
“…However, we and others have consistently documented the lipolytic effects of GH in vivo by means of more precise measures including glycerol concentrations in serum (Moller, Jorgensen, Alberti, et al, ) as well as in the interstitial fluid by means of microdialysis (Gravholt et al, ), and we have also shown that GH increases fatty acid turnover assessed by tracer techniques (Kanaley et al, ; Krag et al, ; Norrelund et al, ). In recent cell studies, we have also demonstrated that GH acutely stimulates glycerol release (Sharma et al, , ). Second, it is inherently difficult to combine human in vivo studies with animal and in vitro models.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, we and others have consistently documented the lipolytic effects of GH in vivo by means of more precise measures including glycerol concentrations in serum (Moller, Jorgensen, Alberti, et al, ) as well as in the interstitial fluid by means of microdialysis (Gravholt et al, ), and we have also shown that GH increases fatty acid turnover assessed by tracer techniques (Kanaley et al, ; Krag et al, ; Norrelund et al, ). In recent cell studies, we have also demonstrated that GH acutely stimulates glycerol release (Sharma et al, , ). Second, it is inherently difficult to combine human in vivo studies with animal and in vitro models.…”
Section: Discussionmentioning
confidence: 60%
“…We recently reported that GH downregulates the mRNA and protein expression of fat specific protein 27 (FSP27), also known as CIDEC, in studies involving GH infusion with and without fasting in healthy young male subjects (mean age ≈ 21 years) (Sharma et al, ), as well as in studies in mice(Sharma et al, ) and in human adipocytes in vitro (Sharma et al, ). Fat‐specific protein 27 is an LD‐associated protein that regulates LD dynamics (Jambunathan, Yin, Khan, Tamori, & Puri, ; Puri et al, ) and lipolysis in adipocytes through downregulation of the transcription and activity of ATGL, the rate‐limiting enzyme in lipolysis (Singh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…3T3-L1 adipocytes were grown and differentiated as previously described [32]. 3T3-L1 (from ATCC: CL-173; passages 4–12) were grown in DMEM, high glucose (4.5 g/L), Glutamax, Pen-Strep and 10% FBS and then seeded at 200,000 cells/well in six-well plates for differentiation into adipocytes.…”
Section: Methodsmentioning
confidence: 99%
“…STAT5 mediates the GH-effects on lipolysis by increasing the transcription of several metabolic genes such as peroxisome proliferator-activated receptor (PPAR)-gamma and fatty acid synthase (73, 74). In addition, both STAT5- and mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK)-dependent intracellular signaling mediate the effects on GH in suppressing mRNA and protein levels of fat-specific protein 27 (FSP27), a negative regulator of lipolysis (75). The importance of FSP27 supression for GH signaling in adipocytes is highlighted by the fact that FSP27 overexpression fully abrogates the effects of GH on lipolysis and insulin resistance in adipose tissue, mainly by inhibiting PPAR-gamma phosphorylation (75, 76).…”
Section: Pathophysiology Of Insulin Resistance In Acromegalymentioning
confidence: 99%